Trade‐offs between three forest ecosystem services across the state of New Hampshire, USA: timber, carbon, and albedo. Issue 1 (8th February 2016) - Lutz, David A.; Burakowski, Elizabeth A.; Murphy, Mackenzie B.; Borsuk, Mark E.; Niemiec, Rebecca M.; Howarth, Richard B.
Abstract: Forests are more frequently being managed to store and sequester carbon for the purposes of climate change mitigation. Generally, this practice involves long‐term conservation of intact mature forests and/or reductions in the frequency and intensity of timber harvests. However, incorporating the influence of forest surface albedo often suggests that long rotation lengths may not always be optimal in mitigating climate change in forests characterized by frequent snowfall. To address this, we investigated trade‐offs between three ecosystem services: carbon storage, albedo‐related radiative forcing, and timber provisioning. We calculated optimal rotation length at 498 diverse Forest Inventory and Analysis forest sites in the state of New Hampshire, USA. We found that the mean optimal rotation lengths across all sites was 94 yr (standard deviation of sample means = 44 yr), with a large cluster of short optimal rotation lengths that were calculated at high elevations in the White Mountain National Forest. Using a regression tree approach, we found that timber growth, annual storage of carbon, and the difference between annual albedo in mature forest vs. a post‐harvest landscape were the most important variables that influenced optimal rotation. Additionally, we found that the choice of a baseline albedo value for each site significantly altered the optimal rotation lengths across all sites, lowering the mean rotation to 59 yr with a high albedo baseline, and increasing the mean rotation to 112 yr given a low albedo baseline. Given these results, we suggest that utilizing temperate forests in New Hampshire for climate mitigation purposes through carbon storage and the cessation of harvest is appropriate at a site‐dependent level that varies significantly across the state.